Respuesta :
Answer:
x= 2
x= -3
Step-by-step explanation:
Solving as normal quadratic equation:
- 2x^2+2x=12
- x^2 +x = 6
- x^2 + x - 6= 0
- x = (-1 ± √(1+4*1*6)/2
- x = ( - 1 ± √25)/2
- x = (-1 ± 5)/2
- x= 2
- x= -3
Roots are 2 and -3
Answer:
x = - 3 or x = 2
Step-by-step explanation:
2x² + 2x - 12 = 0
Divide all the terms by 2 to simplify the terms
That's
x² + x - 6 = 0
Write x as a difference
That's
x² + 3x - 2x - 6 = 0
Factor x out of the equation
That's
x( x + 3) - 2x - 6 = 0
Factor out - 2 from the expression
x(x + 3) - 2( x + 3) = 0
Factor out x + 3 from the expression
That's
( x + 3)(x - 2) = 0
x + 3 = 0 x - 2 = 0
x = - 3 x = 2
Hope this helps you